EFL TEACHERS’ CHANGES IN THE DIGITAL AGE: EXAMINING THE ROLE OF TECHNOLOGY-BASED PROFESSIONAL DEVELOPMENT ON TEACHING PRACTICES - Rifqi, Muhammad Surya (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research aimed to examine the role of technology-based professional development on teachers' changes in teaching practice in the context of an English foreign language classroom. A qualitative case study was used in this study to investigate the impact of technology-based professional development on teachers' classroom practice. The researcher used a purposive sampling method, selecting five participants who had been involved in technology-based professional development. The results show that the professional development programs had an impact on teachers' proficiency, convenience, and confidence in using technology tools in the classroom. The various programs and activities attended by the teachers brought them into various changes in their teaching practices in the classroom. This research is expected to have significance for various stakeholders in the field of education. This research hopefully contributes to the academic discourse around technology integration in education by adding empirical evidence on the growth of effective technology-based professional development in the digital era.